The Effect of Ease of Use and Online Consumer Reviews on Repurchase Intention for Specs Futsal Shoes with Customer Engagement as an Intervening Variable: A Study of Shopee Users in Pontianak - Muhammad Dzaki Rasendriyo; Muhammad Ebuziyya Alif Ramadhan (SAINTIS Publishing, 2026)
This study aims to analyze the effect of Ease of Use and Online Customer Review on Repurchase Intention, with Customer Engagement as an intervening variable among consumers of Specs futsal shoes on Shopee in Pontianak City. This study uses a quantitative approach with an associative design involving 100 respondents selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 3. The results show that Ease of Use has a positive and significant effect on Customer Engagement but does not have a significant effect on Repurchase Intention. Online Customer Review has a positive and significant effect on Repurchase Intention but does not have a significant effect on Customer Engagement. Customer Engagement has a positive and significant effect on Repurchase Intention, but it does not mediate the effects of Ease of Use or Online Customer Review. These findings indicate that repurchase intention for futsal shoes in marketplaces is more strongly influenced by the quality of customer reviews and the level of customer engagement than by perceived platform ease of use alone. This study is expected to provide empirical contributions to the development of digital consumer behavior research, particularly for performance-based sports products.